Enhancement of multicast Proxy MIPv6 with context transfer and multicast fast reroute - Azana Hafizah binti Mohd Aman (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Mobile networking environments have been developing very rapidly. Due to its dynamic nature and imprecise network state information, there are many challenges which need to be addressed especially the need for performance improvement to support mobile multicast. Multicast is defined as the delivery of data to a set of selected receivers. When a mobile node (MN) moves to a new subnet it needs to continue certain services that have already been established at the previous subnet. It is a difficult problem to maintain simplicity and reachability of a MN when moving (handover) from one network to another. Numerous approaches have been proposed including Proxy Mobile IPv6 (PMIPv6) in order to provide better performance. It is mainly proposed to enhance the existing Mobile IPv6 (MIPv6). PMIPv6 adds two nodes called Local Mobility Anchor (LMA) and Mobile Access Gateway (MAG) to cater mobility problems of MIPv6. However to support multicast traffic PMIPv6 has its own problems, since PMIPv6 was initially introduced to support unicast traffic. This thesis introduces an enhancement that aims to improve the performance of multicast session in a multicast communication. It integrates M-PMIPv6 with Context Transfer Protocol (CTP) and Multicast only Fast Reroute (MFR). CTP gives support of the seamless handover based on service continuation using context. MFR is a mechanism for minimizing packet loss in a network when node or link failures occur. Both contribute to the enhancement in handover performance and proposed for MN for quickly re-establishment of their services when the nodes move and change their access routers. The evaluation of the proposed scheme is via simulation and mathematical analysis. The simulation was implemented using NS3 simulator. The performance metrics used for the simulation are handover latency, throughput, packet delivery ratio and packet loss ratio. On the other hand the performance metrics considered for the mathematical analysis are service recovery time, total signaling cost, packet loss and handover latency. The proposed scheme is benchmarked with the standard PMIPv6 enabled with multicast traffic. The proposed scheme offers 63% better handover latency, 66.7% lower packet loss, 70% lower service recovery time, 25% better throughput and 57.7% lower total signaling cost than the benchmarked scheme.